Social Theory Anew: From Contesting Modernity to Revisiting Our Conceptual Toolbox – the Case of Individualization - Araujo-Kakiuchi, K (SAGE Publications Ltd, 2021)
This article argues why core classical sociological notions that are still extremely influential in global sociological thinking need to be reviewed and reconceptualized, as well as to present an example of how this might be done. The discussion is in two parts. First, the article outlines what the author suggests is a major problem of social and sociological theory: the common articulation between modernity, social theory and sociological research, and its negative effects for the production of knowledge in other regions, such as Latin America. The author considers some of the contemporary strategies devised to deal with the difficulties arising from this articulation and proposes a complementary way of overcoming the problem posed. Second, the author backs her argument with a critical analysis of the concept of individualization, one of the earliest and central notions of social theory, based on the results of three empirical studies carried out in Chile over the past decade. © The Author(s) 2020.